Ceramic ultrafiltration and cooling tower blowdown recovery. Issue 10 (October 2015) - Unknown
Abstract : US company Nanostone Water Inc is in the process of introducing its high-density CM-131 ceramic monolith membrane module for use in a broad range of water and industrial treatment applications. Based on material supplied by the company this brief article details some recent pilot-test results that demonstrate the effectiveness and operating efficiency of its ceramic ultrafiltration membrane.